The Role Of The National Narcotics Agency And The Police In Law Enforcement Against The Abuse Of Precursor Drugs - Rivaldo Abdullah (Estudiante Law Journal, 2020)
Drug crime is an international crime (International Crime), organized crime, has an extensive network, has large financial support and has used sophisticated technology. The enforcement of the eradication of narcotics abuse has been carried out by the police and BNN. The National Police and the National Narcotics Agency have released various efforts to eradicate criminal acts of abuse of narcotics and narcotics precursors which are carried out in a preventive, preventive and repressive manner with the aim of making the Indonesian state drug free.